High-frequency surface water changes in the Tagus prodelta off Lisbon, eastern North Atlantic, during the last two millennia - Bartels-Jónsdóttir, Helga Bára; Voelker, Antje H L; Abrantes, Fatima G.; Salgueiro, Emilia; Rodrigues, Teresa; Knudsen, Karen Luise (Marine Micropaleontology, 2015)
A high-resolution sedimentary sequence recovered from the Tagus prodelta has been studied with the objective to reconstruct multi-decadal to centennial-scale climate variability on the western Iberian Margin and to discuss the observations in a wider oceanographic and climatic context. Between ca. 100BC and AD400 the foraminiferal fauna and high abundance of Globorotalia inflata indicate advection of subtropical waters via the Azores Current and the winter-time warm Portugal Coastal Current. Between ca. AD400 and 1350, encompassing the Medieval Climate Anomaly (MCA), enhanced upwelling is indicated by the planktonic foraminiferal fauna, in particular by the high abundance of upwelling indicator species Globigerina bulloides. Relatively light δ 18 O values and high sea surface temperature (SST) (reconstructed from foraminiferal assemblages) point to upwelling of subtropical Eastern North Atlantic Central Water. Between ca. AD1350 and 1750, i.e. most of the Little Ice Age, relatively heavy δ 18 O values and low reconstructed SST, as well as high abundances of Neogloboquadrina incompta, indicate the advection of cold subpolar waters to the area and a southward deflection of the subpolar front in the North Atlantic, as well as changes in the mode of the North Atlantic Oscillation. In addition, the assemblage composition together with the other proxy data reveals less upwelling and stronger river input than during the MCA. Stronger Azores Current influence on the Iberian Margin and strong anthropogenic effect on the climate after AD1750 is indicated by the foraminiferal fauna. The foraminiferal assemblage shows a significant change in surface water conditions at ca. AD1900, including enhanced river runoff, a rapid increase in temperature and increased influence of the Azores Current. The Tagus record displays a high degree of similarity to other North Atlantic records, indicating that the site is influenced by atmospheric-oceanic processes operating throughout the North Atlantic, as well as by local changes.